Islam and Health Policies Related to HIV Prevention in Malaysia - Barmania, Sima (SpringerBriefs in Public Health,, 2018)
This salient text presents a culturally aware public health approach to the HIV epidemic in Malaysia, a country emblematic of the Muslim world's response to the crisis. It explores complex interactions of religion with health as a source of coping as well as stigma and denial, particularly as Islam plays a central role in Malaysian culture, politics, and policy. At the heart of the book, a groundbreaking study analyzes attitudes and behaviors toward prevention among diverse people living with HIV, faith leaders, and government health officials. From these findings, readers gain insight into how health professionals, policymakers, and organizations can create appropriate prevention programs in Malaysia, with implications for other Muslim countries. This timely volume: Situates Malaysia and the Asian Pacific region in the context of the HIV epidemic. Analyzes ways Islamic beliefs can shape perceptions of HIV and prevention policy. Reviews a unique study of stakeholder opinions and practices regarding HIV. Discusses the consequences of Islamic rulings on sex outside marriage. Offers recommendations for effective HIV prevention practice and policy. Islam and Health Policies Related to HIV Prevention in Malaysia is of immediate relevance to researchers studying HIV prevention, social aspects of religion, sexuality, and sex education. Policymakers in health promotion and health education as well as graduate students in sex education, sociology, psychology, and cultural studies should also find it useful.